PKM Pembuatan DARPAS (Dadar Paselang) - Andi Sawe Ri Esso; Nurdiana Nurdiana; Nurjannah Nurjannah; Mustari Mustari; Sitti Hajerah Hasyim (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Changes in food trends, such as the increasing demand for healthy or vegan foods, can be a challenge for rolled pancakes/dadar paselang. If unable to adapt to this trend, dadar paselang may lose its appeal in the market. This can make it difficult to attract consumers and maintain a stable market share. Therefore, innovations in dadar cakes are needed to attract the interest of many people to buy and have an interest in making mochi for consumption or for sale in order to generate economic value that can be marketed both domestically and internationally. The methods used in this activity include lectures, questions and answers or discussions, and training and mentoring conducted in Manggala District, Makassar City for 2 weeks. The results obtained are: (1) The training on making Dadar Paselang was well responded by the participants; (2) The high interest and motivation of the training participants greatly supports the transfer of knowledge and skills from the servants to the training participants, so that the training materials provided can be absorbed by all; and (3) The training products for making dadar paselang can be consumed daily and can be used as community entrepreneurial products.